Evaluating the Psychological Impacts of Patching Treatment on Parents in Qassim Region, Saudi Arabia - Aljohani, Saeed; Al-Mutairi, Rakan (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The previous studies showed that patching treatment for amblyopia in children may have adverse psychological effects on children and families. AIM: The aim of the study was to investigate the reliability and validity of an Arabic version of the Amblyopia Treatment Index questionnaire and to evaluate the psychosocial impacts of patching treatment on parents of amblyopic children. METHODS: This was a cross-sectional study of 239 parents or guardians of amblyopic children who had at least five weeks of patching treatment experience in the past 6 months before enrolment. Eligible parent was either enrolled in the study from Qassim University Medical City eye clinics or referred by optometrists and ophthalmologists from 6 hospitals in Qassim province. Twenty parents were asked to repeat the same questionnaire after 14 days ± 2 days for test-retest reliability. RESULTS: The findings showed good internal validity and reliability for the Arabic version of the Amblyopia Treatment Index questionnaire among Saudi amblyopic patients. The factor analysis revealed that 16 of 21 items were strongly correlated through the questionnaire’s internal consistency ≥0.5 under three factors. Seven items were strongly correlated with the factor of adverse effects of amblyopia treatment. Similarly, seven items were strongly correlated with the lack of amblyopia treatment adherence, and only two were strongly correlated with the factor of social stigma. Reliability tested by Cronbach’s α coefficient showed good internal reliability and consistency (0.774). Cronbach’s α coefficient for the three factors was 0.734 for adverse effect, 0.644 for lack of treatment adherence, and 0.723 for social stigma. There is no significant association between parents’ education level and the final questionnaire score. CONCLUSION: The Arabic version of the amblyopia treatment index questionnaire showed high validity and reliability for factors related to patching therapy and was useful for Saudi children. Treatment of amblyopia in the Saudi community is strongly affected by adverse effects, adherence, and social stigma of adhesive patching.